O papel da percepção de valor e da percepção de risco à saúde no comportamento do consumidor de restaurantes - Filho, Celio Roberto de Oliveira (2023)
The present study examined the mediating role of restaurant value perception in the relationship between food quality, ambiance, and service quality and their impacts on positive word-of-mouth, willingness to pay, and revisit intention. Restaurant qualities, such as food quality, ambiance, and service quality, play a pivotal role in establishment metrics. They directly affect customer satisfaction, their intention to revisit the restaurant, their likelihood to provide positive word-of-mouth, and their willingness to pay more for the offered products and services. Additionally, the study explored the moderating effect of health risk perception on the relationship between ambiance quality and value perception. The relationship between health risk perception and restaurant ambiance is crucial in a post-pandemic context. Consumers are increasingly concerned about hygiene measures, social distancing, and safety in establishments. Health risk perception can influence how customers assess restaurant ambiance quality and their willingness to frequent it. For this purpose, a research was conducted using a self-administered online questionnaire with participants, including students, faculty, and staff from a federal university. The theoretical model was tested using Structural Equation Modeling (SEM). Tests were performed using SmartPLS 4.0 software. It was found that the relationship between service quality and dependent variables is fully mediated by value perception. Regarding food quality, full mediation only occurs with willingness to pay, while the others show partial mediation. Ambiance quality is unrelated to dependent variables until the 'Health Risk Perception' moderator is added to the model. This study contributes to understanding consumer preferences, fears, and expectations. Its theoretical contribution lies in the proposal of value perception mediation and the moderation of health risk perception and location.